Makna Rezeki dalam Al-Qur'an: Tafsir dan Implikasi Konseptual - Baihaki, Iki (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Sustenance, as a central concept in the daily lives of Muslims, encompasses spiritual, moral, and social dimensions that provide a holistic perspective on understanding sustenance. This research aims to identify and analyze the concept of sustenance found in the Quran, exploring the profound meanings contained within it. The research methodology employed is qualitative analysis of Quranic verses specifically referring to the concept of sustenance. The analytical approach includes the identification of verses, understanding historical, linguistic, and cultural contexts, as well as synthesizing the concepts of sustenance expressed in the Quran. The study yields a deep understanding of the concept of sustenance in the Quran, identifying variations in meaning, the contexts of usage, and the moral messages contained in verses addressing sustenance.